Composição química e atividades biológicas de Ocimum gratissimum L. - Silva, Lenise de Lima (2009)
Ocimum gratissimum L. (Lamiaceae), known as alfavaca, is widely distributed in tropical and warm-temperature regions. It is used as a food flavoring and for medicinal purposes against infectious diseases. Its biological properties are attributed to the presence of thymol or eugenol-rich essential oils. This study describes qualitative and quantitative variations in essential oils from stems, inflorescences and leaves of O. gratissimum L. grown in southern Brazil, in two harvest periods. The evaluation of eugenol content, antibacterial activity and toxicity of the different ethanolic extracts from dried aerial parts of O. gratissimum were studied. Afterwards, the essential oil from fresh inflorescences had its antibacterial activity, toxicity and chemical composition determined. The essential oils were obtained by hydrodistillation and analyzed by GC/MS. The extracts were obtained by maceration, soxhlet, ultrasonic cleaning bath, ultrasonic horn and microwave-assisted extractions. Eugenol content was determined by GC-FID using the pure compound isolated from aerial parts of the plant as reference. Antibacterial activity was assayed by microdilution method as established by CLSI/NCCLS. Toxicity was verified by brine shrimp (Artemia salina L.) lethality test. The major compounds of all essential oils were eugenol (52.6 - 89.2 %) and γ-muurolene (6.2 35.3 %). The harvest season influenced only the yields of inflorescence and stem essential oils. The low seasonal variation of eugenol in the essential oil of the leaves indicated that these are the best source to obtain this compound. Inflorescences essential oil was bacteriostatic (MIC between 0.5-2 mg/mL) and bactericidal (MBC between 1-4 mg/mL) against all strains tested. Significant differences (P<0.05) among the extractive methods used to the obtention of ethanolic extracts were observed in all analyses. Higher antimicrobial activity was verified to extracts compared to the essential oil tested against S. aureus ATCC 25923 and clinical isolate of B. cereus, MRSA (MIC of 0.66 mg/mL), ESBL and Shigella flexneri (MIC of 1.32 mg/mL). Bactericidal activity of the extracts was verified in Grampositive bacteria. Eugenol content did not explain all differences obtained among the antimicrobial activities of the tested extracts. The results suggest synergistic action among phyto-constituents. Maceration was considered the best extraction process considering the biological activities of all extracts. The antimicrobial avaliation results confirmed the brine shrimp lethality test as predictive method for this activity.